Comparative study of carbamazepine and sodium valproate on - free triiodothyronine, in paediatric patients in teaching hospital - Dr. Dharmender Gupta; Dr. Atul Kumar (Pediatric Review: International Journal of Pediatric Research, 2019)
Background: This study was conducted in Department of Paediatrics, Sanjay Gandhi Memorial Hospital, Mangolpuri, Delhi 83. Objective of the study was to measure and compare TSH, FT4, FT3, hormone level before, after 3 month and 6 months after starting Carbamazepine and Sodium Valproate monotherapy in 2-12 years old children. Method: This prospective study performed in 82 newly diagnosed Paediatric patients with partial/ generalized seizures, subdivided into two groups: 42 patients treated with carbamazepine and 40 patients treated with valproic acid. 30 age and sex matched subjects served as controls. Free triidothyronine (FT3) evaluated at baseline and at 3rd and 6th months in all patients and in control group. Height, weight, BMI and liver function test were also evaluated at baseline at 3rd and 6th months in all patients and in control group. Results: At baseline thyroid function was normal in all epileptic patients in controls. Decrease in mean FT3 level (from 5.57±0.90 pmol/l at baseline, 5.51±0.75 pmol/l after 3 months and 5.13±0.78 pmol/l after 6 months of therapy) was seen in CBZ group even though that was not significant (p=0.434 at 3 months, p=0.372 at 6 months). In VPA treated patients there was no statistically significant difference found in FT3level after 3 and 6 months of therapy. Conclusion: Our data suggest that VPA monotherapy does not alter FT3 level. On the contrary alterations of thyroid hormones occur in CBZ treated children, however the patients remained euthyroid.